Influence and Consequences of Depression in Cyberbullying Manifested In Adolescence - Martinez-Lanz, Patricia (Advances in Social Sciences Research Journal, 2016)
The use of mass media, especially social networks is part of a lifestyle in the world mainly in adolescents. The currently access to the network is seeing high: 80% of adolescents have Internet access, and 70% are online daily, so the information and dissemination has become difficult to reduce, as well as the need they have of remaining on the network. The aim of the study was to determine the relationship of the main variables involved in this phenomenon, including domestic violence, levels of depression, and self-esteem in adolescents between 12 and 16 years. The questionnaire applied to the participants consisted of 5 parts: 1) general information of the subject; 2) type of environment in which the subject lives; 3) self-esteem; 4) type of participation on cyberbullying, being victim or aggressor; 5) depression. The results showed that young people with high levels of violence have high levels of cyberbullying, as well high levels of depression. Subjects who had high self-esteem were observed with low levels of domestic violence and participants with low levels of depression showed a low level of cyberbullying. On the other hand, subjects with low levels of cyberbullying have adequate self-esteem as well as participants who reported lower levels of depression. Therefore depression is a factor that is directly related to the conduct of cyberbullying, as well as the style of home life that adolescents have today